A Rare Subtype of Non-small Cell Lung Cancer: Report of 159 Resected Pathological Stage I–IIIA Pulmonary Lymphoepithelioma-Like Carcinoma Cases - Jiang, Rong-Rong; Feng, Xiao-Li; Zhu, Wen-Ting; Guo, Man-Xia; Tan, Xue-Li; Jiang, Xiao-Juan; Dou, Xiao-Meng; Liu, Li (Frontiers in Surgery, 2021)
Background: The current study analyzed resected stage I–IIIA pulmonary lymphoepithelioma-like carcinoma (LELC) cases to define the clinical characteristics, prognosis and long-term outcomes of resected LELC, with the purpose of guiding clinical management for this rare tumor. Methods: Resected stage I–IIIA LELC, adenocarcinoma (ADC) and squamous cell carcinoma (SCC) cases from our center were enrolled. Propensity score matching (PSM) was applied to minimize the selection bias. Overall survival (OS) and disease-free survival (DFS) were compared between groups. Multivariate analyses were performed to identify the prognostic factors, and a nomogram was developed. Results: A total of 159 LELCs, 2,757 ADCs, and 1,331 SCCs were included. LELC, dominated among younger patients and non-smokers. LELC was a poorly differentiated disease that lacked driver gene mutations and was positive for immunohistochemistry indicators of squamous cell lineage. Survival analyses revealed that OS was significantly better for LELC than for other common non-small cell lung cancers (NSCLCs) both before PSM (all P < 0.001) and after PSM (all P < 0.05). Further analyses revealed that early pathological node stage and preoperative albumin level ≥35 were identified as independent prognostic factors favoring OS and DFS. Conclusions: LELC, dominated among younger and non-smoking populations, lacked driver gene mutations and was positive for immunohistochemistry indicators of squamous cell lineage. The survival outcome of LELC was better than other common NSCLCs.